Unmet emotional, interpersonal, and treatment needs in patients with borderline personality disorder - Kantor, Krystof; Prasko, Jan; Ociskova, Marie; Holubova, Michaela; Nesnidal, Vlastimil; Vanek, Jakub; Minarikova, Kamila; Hodny, Frantisek; Slepecky, Milos; Zatkova, Marta (Neuro-endocrinology letters, 2022)
OBJECTIVE: Needs of psychiatric patients may be to a various degree frustrated. A sole focus on treatment effectiveness can lead to the omission of other patient's needs. Patients with borderline personality disorder present high demands on health and social services that often remain unmet. The review aims to identify common unmet needs of patients with BPD, map the areas in which they appear, and identify ways to manage them. METHOD: The PubMed database was used by applying the following key terms: "borderline personality disorder" and "needs" supplemented by a combination of "borderline personality disorder" and "unmet needs"; "treatment"; "therapy"; "management", "quality of life", "pharmacotherapy", "psychotherapy". the Papers were selected from a period between Jan 1, 1990, and Nov 30 2020. Primary keyword search yielded a total of 502 articles, of which 225 articles met the inclusion criteria and were subjected to a complete inspection. Secondary contributions from reference lists of the primary sources were examined, evaluated for suitability, and added to the primary document list (n = 182). After an evaluation of the relevance, a total of 197 papers were included in the review process. RESULTS: Recognizing patients' unmet needs with borderline personality disorder emphasises the importance of a comprehensive patient assessment. The diagnosis of comorbidities is also essential, especially with bipolar disorder and posttraumatic stress disorder, as comorbid conditions may require different therapeutic approaches. Traditional treatments of BPD tend to be demanding both in time and funding. However, alternatives are being developed to overcome these shortcomings by introducing methods focused on specific goals. Furthermore, supporting the patient's responsibility in the treatment choice can lead to better improvements. CONCLUSIONS: There is a need for further studies that will focus on the needs of this patient group and the possibilities of their treatment in psychotherapy, using psychotropic drugs, or social interventions. The development of step-by-step treatment models, adjunctive treatments, and technology-based interventions can bring greater access to care and reduce costs, especially for newly diagnosed patients or patients waiting for comprehensive treatment.
Keywords: Psychotherapy; emoce; hraniční porucha osobnosti; Bipolar Disorder; Emotions; komorbidita; lidé; bipolární porucha; Comorbidity; psychoterapie; Borderline Personality Disorder; Humans